Relationship among anthropometric characteristics, handgrip strength and throwing velocity in adolescent handball players - Zapartidis, I.; Palamas, A.; Papa, M.; Tsakalou, L.; Kotsampouikidou, Z. (Journal of Physical Education and Sports Management, 2016)
Objectives: was to investigate the relationship among maximal isometric handgrip strength, ball throwing velocity and dribble as well as the influence of basic anthropometric characteristics on these parameters in adolescents male and female handball players. Methods: The sample consisted of 119 subjects (75 boys and 44 girls) adolescent handball players aged 13.44 ± 0.35 years with 2.77 ± 0.91 yrs training experience. Variables included height; body mass, BMI, arm span, hand length, hand span, maximal isometric handgrip strength, and throwing velocity. Statistics included a) Pearson correlation analysis to evaluate the relationship among the measured variables, b) stepwise regression analysis for the predictability control of selected anthropometric characteristics and handgrip strength against ball throwing velocity as well as between anthropometric characteristics and handgrip strength and c) independent sample t - test to compare sex differences in ball velocity and maximal isometric handgrip strength. Results: Ball throwing velocity was found to be moderately correlated to all anthropometric measures. Handgrip strength showed a higher correlation with ball velocity, and moderate correlation with hand length, arm span and body height, while 30-m speed dribble time showed a low correlation with ball velocity respectively. Stepwise regression analyses revealed that two of the independent variables (handgrip strength and arm span) contribute significantly to the prediction of ball velocity. Male athletes outperform significantly in ball velocity and hand grip strength.